An investigation of antecedents and consequences of brand love in India. Issue 3 (7th September 2015) - T.C. Melewar, Dr Bang Nguyen; Professor Bill Merrilees, Professor; Garg, Ruchi; Mukherjee, Jaydeep; Biswas, Soumendu; Kataria, Aarti
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the factors that drive consumer love toward a brand and the opportunities a consumer's love create for a brand in India. Design/methodology/approach – A total of 23 in-depth interviews were conducted with consumers. The interview transcripts were analyzed through thematic analysis using qualitative software Nvivo10. Findings – This paper proposes a conceptual model where respect, brand experience, and brand reputation have been identified as factors driving brand love and affective commitment, consumer citizenship behavior, repurchases intention, consumer forgiveness, and attitude toward the extension as outcomes of brand love. Practical implications – Consumers bond with brand helps in mitigating the feelings of transgressions by the brand, and also protects brand from negative word of mouth. Consumers who are in love with a brand show positive attitude toward its extensions. These results provide pointers to brand managers on how to protect and expand the business. Originality/value – The extant brand love research seems to be solely in the western context. To the best of the author's knowledge, this is the first study of its kind that empirically investigates antecedents and consequences of brand love in India.